The Effect of Caffeine Ingestion and Carbohydrate Mouth Rinse on High-Intensity Running Performance - Mark Germaine; Kieran Collins; Marcus Shortall (MDPI AG, 2019)
The aim of the current study was to investigate whether carbohydrate mouth rinsing works synergistically with caffeine to augment high-intensity running in a fed state. Eight participants completed a total of three trials; (1) placebo (PLA) trial (placebo capsule + placebo mouth rinse), (2) caffeine (CAF) trial (400 mg caffeine + placebo mouth rinse) and (3) carbohydrate mouth rinse + caffeine (CMR + CAF) trial (400 mg caffeine + 6% carbohydrate mouth rinse). Each trial consisted of a 45 min steady-state run at 65% VO2max, followed by 90% VO2max high-intensity intervals (HIIT) at 1 min and subsequently by a 1 min recovery walking at 6 km·h−1, until exhaustion. Both CAF (46.8 ± 20.1 min) and CMR + CAF (46.9 ± 18.4 min) time to exhaustion were significantly greater than the PLA group (36.2 ± 14.8 min, p < 0.001). Post hoc analysis revealed that there was a significant increase in time to exhaustion between PLA and CMR + CAF (p = 0.006) and PLA and CAF (p = 0.017) but not between CAF and CMR + CAF (p = 0.99). In conclusion, we provide novel data that suggest that caffeine alone would likely suffice as an ergogenic aid during high-intensity running while in a fed state.